The State in the Legal Philosophy of Giorgio del Vecchio - García Belaunde, Domingo (1972)
This paper focuses on a study of the works of Giorgio del Vecchio and his contributions to the philosophy of law. In this sense, the author analyzes del Vecchio's trilogy: i) the philosophical presuppositions of the concept of law; ii) the concept of law and iii) the concept of the nature and principle of law. The author contextualizes the period in which del Vecchio develops his works in order to situate his analysis: after the First World War. Likewise, the article also contemplates the conceptions that del Vecchio developed on ethics and its influence on the conception of the State, law and the theory of the State. Finally, the author reflects on the validity of del Vecchio's thoughts today and expresses his position on the relevance of his thought for further analysis in the philosophy of law.